BERMISI DALAM MASYARAKAT MAJEMUK MELALUI DIALOG DAN KERJA SAMA - Jonidius Illu; Enry Yakobus Duapadang; Robert P Borrong (Sekolah Tinggi Teologi Arastamar Bengkulu, 2024)
Indonesia is a pluralistic society because its citizens consist of various ethnic groups, races, religions, and social groups. Missions in a pluralistic society certainly have their own characteristics and uniqueness. This paper is a study of church missions in the context of a pluralistic society, taking West Sulawesi as the location of the research. The research method used to write this article is a qualitative method in the library, supplemented by field observations by observing the phenomena of church members' lives and interviews with several church leaders. This study employs a qualitative method with a case study approach, involving in-depth interviews with church leaders, congregation members, and other religious figures involved in interfaith dialogue and cooperation.. The results of the study indicate that honest and open dialogue, along with cooperation in social and humanitarian projects, can be effective tools for building mutually beneficial relationships between religious communities. This approach not only strengthens the role of the church in society but also helps to overcome prejudices and conflicts that may arise due to religious and cultural differences. These findings highlight the importance of cultural understanding, empathy, and communication skills in the implementation of missions in a pluralistic society. The study concludes that missions focusing on dialogue and cooperation are not only relevant but also essential in promoting peace and harmony in a pluralistic society. Practical recommendations are provided for churches and mission organizations in developing programs that support interfaith integration and cooperation, as well as advocating for policies that encourage inclusiveness and tolerance in society.